College Adjustment of First Year Students: The Role of Social Anxiety - Ruseno Arjanggi; Luh Putu S. Kusumaningsih (Universitas Ahmad Dahlan, 2016)
AbstractThis research aims to analyze the correlation between social anxiety and college adjustment. 436 undergraduate psychology students of five universities in Central Java were involved in this study. All respondents completed a questionnaire about student adjustment to college, and social anxiety scale. Canonical correlation was conducted to analyze the data. The result showed that fear of negative evaluation correlates with academic and personal-emotional adjustment, but not with social adjustment and institutional adjustment, while social avoidance and distress correlate with all of the dependent variables. This study suggests about the role of social anxiety to college adjustment. These findings investigate further discussion about appropriate intervention to address adjustment problems among college students.Keywords: Academic adjustment, social adjustment, personal-emotional adjustment, institutional adjustment, social anxiety.